Effectiveness Of Using Audio, Visual, And Multimedia Media in Arabic Language Learning in the Digital Era - Hanik, Elok Fikril; Nashihah, Riris Fikriyatun; Salam, Muhammad Badrus (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2025)
This study aims to examine the effectiveness of using audio, visual, and multimedia media in teaching Arabic in the increasingly developing digital era. In the context of modern education, the utilization of technology is crucial for enhancing the quality of learning. By employing a mixed-method approach, this research combines quantitative and qualitative data to provide a more comprehensive picture of the impact of media on students' learning outcomes. The findings indicate that the use of audio media significantly contributes to the improvement of students' listening skills, which is an essential aspect of mastering the Arabic language. Additionally, visual media, such as images and graphics, have proven effective in reinforcing vocabulary comprehension, allowing students to more easily remember and use new words in the appropriate context. Audiovisual media, which combines audio and visual elements, creates a more interactive and engaging learning experience, leading to greater student involvement in the learning process. Furthermore, this study also found that the use of interactive media, such as educational applications and online learning platforms, can significantly enhance student participation. Thus, this research highlights the importance of integrating appropriate media in Arabic language teaching to improve student motivation and learning outcomes, as well as providing recommendations for educators to leverage technology in the learning process.